School-Day Physical Activity and Academic Achievement: Mediators Among US Elementary Students. Issue 2 (16th February 2023) - Elish, Paul N.; Bryan, Cassandra S.; Boedeker, Peter; Saksvig, Emilie R.; Calvert, Hannah G.; Kay, Christi M.; Meyer, Adria; Gazmararian, Julie A.
ABSTRACT: Introduction/Purpose: It is recommended that children get 60 min of moderate-to-vigorous physical activity (MVPA) daily. Previous research on MVPA's effect on academic achievement (AA) is inconclusive, and few studies have investigated the relationship's mediators. This study assessed whether cardiorespiratory fitness (CRF) and body mass index (BMI) mediate the school-based MVPA–AA relationship. Methods: Grade 4 students ( n = 4936) were recruited in 40 elementary schools from a large, diverse US public school district. Students wore accelerometers measuring school-day MVPA for 15 d across three semesters. Academic performance data were collected from grades 3 to 5, and CRF and BMI were measured in grades 4 and 5. Multilevel modeling assessed whether BMI and CRF were mediators in the cross-sectional and longitudinal MVPA–AA relationship. Stratified analyses assessed differences in mediation by sex. Results: Cross-sectional analyses found that school-day MVPA had a significant positive indirect effect through higher CRF for various teacher-assigned course grades and English language arts standardized test scores (all P < 0.001). Cross-sectional analyses found no significant mediation through BMI. Longitudinal analyses found that a 10-min increase in daily grade 4 school-day MVPA was associated with higher CRF with 0.16-, 0.09-, and 0.14-point increases in grade 5 math, reading, and writing grades, respectively (all P < 0.001). Decreased grade 4 BMI mediated a 0.06-point increase and 0.05-point increase for grade 5 math and writing grades, respectively (both P < 0.001). The total effect of school-day MVPA on AA was negative but negligible in practical terms. Stratified analyses found more evidence for positive indirect effects through CRF among females. Conclusions: School-day MVPA can positively impact AA through increased CRF and (to a lesser extent) lowered BMI, but the effect is negligible. The negative total effects and positive indirect effects suggest that there are other unmeasured mediators. It remains important for schools to protect school-based physical activity given its health benefits.